2012
DOI: 10.1308/003588412x13171221502347
|View full text |Cite
|
Sign up to set email alerts
|

Gastric perforation in an adult male following nasogastric intubation

Abstract: IntroductionSpontaneous gastric perforation is a well known surgical emergency which carries significant mortality and morbidity. Well documented causes in adults include peptic ulcer disease, drugs such as non-steroidal and gastric malignancy. Iatrogenic causes still remain relatively rare. We report an interesting case of an acutely unwell young man who developed gastric perforation secondary to nasogastric intubation.Case ReportA 32 year old man initially treated for gastroenteritis underwent laparotomy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
(11 reference statements)
0
13
0
3
Order By: Relevance
“…We also strongly believe that the injury may be associated with nasogastric tube based on the visualisation of tube protrusion through the stomach defects during exploratory laparotomy. Perhaps it was related to pressure ischemia exerted on stomach mucosa by nasogastric tube suction and by relatively rigid nasogastric tubes [ 10 ]. Other proposed mechanisms include direct effect of intraperitoneal chemotherapy [ 11 ] and thermal injury caused by inflow and outflow catheters during infusion of HIPEC [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also strongly believe that the injury may be associated with nasogastric tube based on the visualisation of tube protrusion through the stomach defects during exploratory laparotomy. Perhaps it was related to pressure ischemia exerted on stomach mucosa by nasogastric tube suction and by relatively rigid nasogastric tubes [ 10 ]. Other proposed mechanisms include direct effect of intraperitoneal chemotherapy [ 11 ] and thermal injury caused by inflow and outflow catheters during infusion of HIPEC [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Burad et al [ 17 ] and Hirshoren et al [ 18 ] both reported serious soft tissue injuries prompting intervention and subsequent intensive care evaluation post-procedure. Gastric perforation was described by Daliya et al [ 19 ] and Hynh et al [ 20 ]; both resulted in diagnostic re-operations and consequent surgical repair. Other high morbidity complications, including esophageal perforation, were identified as well.…”
Section: Resultsmentioning
confidence: 99%
“…Because the pathology is progressive, we also considered administration of steroids for early treatment. However, due caution is required for the administration of steroids in cases where differentiation between inflammatory and noninflammatory arteriopathy is difficult because it can increase vascular fragility [3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%